Carbon nanotubes and (Mg10Ni)85Ce15 synergistically activate Mg-Al alloy waste for efficiently hydrolysis hydrogen generation. (15th September 2022) - Hou, Kaiming; Hou, Xiaojiang; Ye, Xiaohui; Li, Danting; Suo, Guoquan; Xie, Lishuai; Shu, Qiang; Cao, Qianhong; Bai, Jing
Graphical abstract: Highlights: MNC15 and CNTs were firstly and simultaneously added to activate Mg-Al alloy waste. MA-5CNTs-10MNC15 can generate 806.6 mL·g −1 H2 with 0.92 H2 yield at 328 K. The rate-controlling steps in different hydrolysis stages were investigated. Activation mechanism based on nucleation and growth up of Mg(OH)2 is discussed. Abstract: Hydrogen generation via Mg-Al alloy waste (MA) hydrolysis is regarded as a potential and promising strategy for portable hydrogen generators. An efficient modification method to obtain rapid kinetics and high yield for hydrolysis H2 generation needs to be further explored. At present, it is difficult to achieve rapid and high-yield hydrogen production process while maintaining high capacity. In this work, carbon nanotubes (CNTs) and (Mg10Ni)85 Ce15 (MNC15 ) were creatively employed as additives to synergistically activate MA. Different content of additives was respectively or simultaneously employed through high energy ball milling process to investigate their synergistic effect. The results show that the simultaneous addition of MNC15 and CNTs can significantly improve the hydrolysis kinetics and hydrogen yield of MA. MA-5CNTs-10MNC15 can generate 806.6 mL·g −1 H2 with 0.92 yield at 328 K with initial 10 min. The thermodynamic behaviors of MA and activated MA were investigated in detail and the rate-controlling steps were further analysed via different hydrolysis stages. When 10 wt% CNTs added, Ea decreases from 33.6 kJ·mol −1 to 8.1 kJ·mol −1 . The Ea of MA-5CNTs-10MNC15 can reach to 15.8 kJ·mol −1 . The rate-controlling steps were confirmed to transform from three-dimensional interface to one dimensional-diffusion process. The synergistic activation effect was creatively explained by nucleation and growth up mechanism on the basis of the increased nucleation rate by MNC15 and enlarged growth space by CNTs. This work may provide a novel and efficient modified strategy for transforming Mg alloy waste into pure H2, which may pave way for the application of portable hydrogen generators.